INTRODUCTION INTO ANATOMICAL HISTOLOGICAL TERMINOLOGY. NOUN, GRAMMAR CATEGORIES OF NOUNS. DETERMINATIONS OF GENDER, STEM, VOCABULARY FORMS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This is the abstract of the histological anatomical terminologies and grammar categories of nouns. In this article there is a brief information about aforementioned topic. I have also included information about how to determine gender, stem, and vocabulary forms of the anatomical histological words